2021
DOI: 10.1155/2021/1815098
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide Globular Adiponectin Ameliorates Hypoxia/Reoxygenation-Induced Cardiomyocyte Injury by Inhibiting Both Apoptosis and Necroptosis

Abstract: Adiponectin is a small peptide secreted and a key component of the endocrine system and immune system. Although globular adiponectin protects myocardial ischemia/reperfusion-induced cardiomyocyte injury, the protective mechanisms remain largely unresolved. Using a neonatal rat ventricular myocyte hypoxia/reoxygenation model, we investigated the role of its potential mechanisms of necroptosis in globular adiponectin-mediated protection in hypoxia/reoxygenation-induced cardiomyocyte injury as compared to apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…To further investigate our observations from studies in WT and Ad‐KO mice, we also used the cellular models of primary adult rat cardiomyocytes or H9c2 cells subjected to hypoxia. Previous studies have indicated that adiponectin reduced apoptosis induced by chronic intermittent hypoxia and inhibited hypoxia/reoxygenation‐induced necroptosis and intrinsic apoptosis via AdipoR1‐APPL1‐AMPK signaling in H9c2 cells 47,48 . We found that autophagy flux was enhanced following adiponectin treatment in normoxic or hypoxic conditions.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…To further investigate our observations from studies in WT and Ad‐KO mice, we also used the cellular models of primary adult rat cardiomyocytes or H9c2 cells subjected to hypoxia. Previous studies have indicated that adiponectin reduced apoptosis induced by chronic intermittent hypoxia and inhibited hypoxia/reoxygenation‐induced necroptosis and intrinsic apoptosis via AdipoR1‐APPL1‐AMPK signaling in H9c2 cells 47,48 . We found that autophagy flux was enhanced following adiponectin treatment in normoxic or hypoxic conditions.…”
Section: Discussionmentioning
confidence: 50%
“…hypoxia inhibited hypoxia/reoxygenation-induced necroptosis and intrinsic apoptosis via APPL1-AMPK signaling in H9c2 cells. 47,48 We found that autophagy flux was enhanced following adiponectin treatment in normoxic or hypoxic conditions. Importantly, to verify the functional significance of adiponectin-stimulated autophagy, we generated an autophagy-deficient cell model using CRISPR to delete Atg7.…”
Section: Discussionmentioning
confidence: 87%
“…Even though the causal relationship between necroptosis and inflammation is more complicated, the peaked expression of TNF-α and necroptotic proteins occurred simultaneously on day 14 after AD, suggesting that TNF-α might be an important trigger of AD necroptosis. The MAPK pathway, the downstream activation of oxidative stress, activated the inflammatory factor TNF-α, which is a key controller in the process of necroptosis via the modification of RIP1 and RIP3 ( 8 , 56 59 ). Herein, EGCG-NPs significantly decreased the expression of ERK1/2 and p-p38 in the epidermis, indicating that EGCG-NPs regulated necroptosis after AD by oxidative stress/MAPK/inflammation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin (APN) is a fat factor secreted by the adipose tissue, which contributes to maintaining cardiovascular health [70]. APN has been reported to improve cardiomyopathy [71,72]. Further analysis showed that H 2 S therapy restored HFDinhibited APN levels and suppressed HG-induced cardiac ER stress.…”
Section: Hydrogen Sulfide Improves Diabetic Cardiomyopathy By Regulat...mentioning
confidence: 99%